2020
DOI: 10.2139/ssrn.3639551
|View full text |Cite
|
Sign up to set email alerts
|

Twitter and Census Data Analytics to Explore Socioeconomic Factors for Post-COVID-19 Reopening Sentiment

Abstract: Investigating and classifying sentiments of social media users (e.g., positive, negative) towards an item, situation, and system are very popular among the researchers. However, they rarely discuss the underlying socioeconomic factor associations for such sentiments. This study attempts to explore the factors associated with positive and negative sentiments of the people about reopening the economy, in the United States (US) amidst the COVID-19 global crisis. It takes into consideration the situational uncerta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Rahman et al. also explored socioeconomic factors that are associated with sentiments of people about reopening the economy using Twitter and Census data, and found that people with lower education level, lower income, and higher house rent are more interested in reopening the economy [9] . These studies were generally focused on the relatively short-term effects of lockdown or stimulus policies with respect to certain consumer socio-demographics in limited geographies.…”
Section: Introductionmentioning
confidence: 99%
“…Rahman et al. also explored socioeconomic factors that are associated with sentiments of people about reopening the economy using Twitter and Census data, and found that people with lower education level, lower income, and higher house rent are more interested in reopening the economy [9] . These studies were generally focused on the relatively short-term effects of lockdown or stimulus policies with respect to certain consumer socio-demographics in limited geographies.…”
Section: Introductionmentioning
confidence: 99%
“…This disease is imposing tremendous pressure on the health care system [8]. Besides, COVID-19 is affecting the mental health of people in the form of mass fear, panic, and uncertainties [10][11][12]. Because of the escalation of the pandemic, there has been a huge increase in the personal stockpiling of necessary goods (e.g., food staples, toilet paper, cleaning supply) which is unsettling the balance in the demand and supply of consumer goods [6].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, not all the indicators from the original datasets are readily meaningful for pandemic research and it is necessary to effectively screen out attributes to highlight the desired characteristics of socioeconomic measurements. For example, the Census Bureau [19] provides thousands of fields for multiple geographic scales each year, but less than 20 factors are widely recognized and used in COVID-19-related analysis and studies [11,20]. Socioeconomic factors such as the policy stringency index [21,22] are broadly accessed and utilized at country level, but not at the state-level in the USA.…”
Section: Discussionmentioning
confidence: 99%